Reconciliation and truth in Kashmir: a case study. (October 2014) - Iqbal, Sajid; Hossain, Zoheb; Mathur, Shubh
The past two decades have witnessed two distinct phases of the conflict in Indian Administered Kashmir. What started out as a civil conflict in 1989, with active Kashmiri participation in an armed struggle for secession from India, based on the right to self-determination, as recognised by the United Nations Security Council has since transformed into a peaceful and non-violent agitation for the same right. The conflict has spawned massive violations of human rights, by both Indian security forces and 'militants' clashing with them, the former outnumbering the latter: the average Kashmiri has borne the brunt in either case. Though a fraction of what it was even seven years ago, the violence continues, causing severe social, economic and psychological crises among Kashmiris. This paper attempts to start a discussion on these problems, within a transitional justice framework, and explores the possibility of establishing a truth commission to address human rights violations committed by both sides of the conflict. The author contends that the transition in Kashmir from a 'conflict' to a 'post-conflict' situation has already begun, and that establishing a truth commission is an important way to formalise that break. The article is based on primary research, through interviews conducted in Kashmir in August 2009 with leaders of separatist and mainstream political parties, and with victims' groups, to elicit their opinions on the need for a truth commission, and to ask them about the scope, composition and general powers they would envisage for any such commission, if it were established.